Steam reforming of methane over nickel catalyst using a one-dimensional model - Rakhi , Rakhi; Günther, Vivien; Richter, Jana; Mauss, Fabian (International Journal of Environmental Sciences, 2022)
Steam reforming of hydrocarbons is a well established chemical process which provides synthesis gas (H2 and CO). These synthesis products can hence be converted to numerous valuable basic chemicals. For the industrial application of steam reforming, a detailed understanding of the process is a prerequisite. Models that capture the detailed homogeneous and heterogeneous reaction kinetics and the comprehensive transport processes as well as their interaction have the potential to optimize the catalytic process without expensive experimental campaigns. In this paper, a detailed investigation has been done using a multi-step reaction mechanism for modeling steam reforming of methane over nickel-based catalyst using a one-dimensional (1D) model, LOGEcat [1]. The model is applicable to the simulation of all standard after-treatment catalytic processes of combustion exhaust gas along with other chemical processes involving heterogeneous catalysis, such as, the Sabatier process [27]. It is a 1D tool, thus is computationally cost effective and is based on a series of perfectly stirred reactors (PSR). The model is used to perform the simulations for various reactor conditions in terms of temperature, pressure, flow rates and steam-to-carbon (S/C) ratio. Several chemical reaction terms, such as, selectivity, yield, conversion, and mole fraction have been shown with respect to the varied parameters and the results are compared with 2D simulations and experimental reference data. We report a very good agreement of the various profiles produced with 1D model as compared to the reference data. Note that the main aim of this study is to check how far the 1D model can capture the basic chemistry for modeling steam reforming of methane over nickel-based catalysts. It is interesting to note that the cost effective reduced order model is capable to capture the physics and chemistry involved with a multi-step reaction mechanism showing the predictive capability of the model. This study forms the basis for further analysis towards the thermochemistry of the species to develop a kinetically consistent reaction mechanism.